2000
DOI: 10.1364/ol.25.000484
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-optical effect and saturation of nonlinear absorption induced by gray tracking in a 532-nm-pumped KTP optical parametric oscillator

Abstract: We present experiments that show that gray tracking modifies the parametric gain and the generated wavelengths of a KTP optical parametric oscillator pumped at 532 nm near degeneracy. These perturbations occur over a limited range of pump intensity. We propose a satisfactory model that takes into account photochromic damage, the thermo-optical effect, and the combined processes of creation and saturation of a two-photon absorber at 532 nm. The temperature dependence of Sellmeier equations of KTP is also establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 6 publications
0
12
0
2
Order By: Relevance
“…The measurements show that the absorption increases but not on the level as described in [8,10,9,19,69]. Our measurements were performed on the crystal which was not illuminated by blue light for more than 4 days before.…”
Section: Optimal Focusing In the Crystal And Thermal Lensingmentioning
confidence: 82%
See 1 more Smart Citation
“…The measurements show that the absorption increases but not on the level as described in [8,10,9,19,69]. Our measurements were performed on the crystal which was not illuminated by blue light for more than 4 days before.…”
Section: Optimal Focusing In the Crystal And Thermal Lensingmentioning
confidence: 82%
“…These marks need long time to disappear on their own and the crystal in this case rather demands an active healing treatment known as thermal annealing [47]. The investigations by [8,10,9,19,69] have shown that the transparency of the crystal changes after the exposure to the blue pump beam. Above mentioned papers measure the absorption after the exposure.…”
Section: Optimal Focusing In the Crystal And Thermal Lensingmentioning
confidence: 99%
“…Subscripts 1 and 2 represent fundamental and second harmonic, respectively. The degree of phase mismatching is evaluated by 14k =2w(n2 -n1)/c0 (5) where c0 is speed of light in vacuum. When 4k is zero, phase matching condition is fulfilled.…”
Section: Analysis Methods Of Crystal Temperature Changementioning
confidence: 99%
“…Um problema técnico deste tipo de cristalé a formação de centros de cor (gray tracking) [39,40,41], principalmente na frequência do bombeio, o que aumenta a absorção do cristal e, consequentemente, o limiar de oscilação do OPO. Por este motivo, a operação de nosso OPO em regime contínuo (CW) sóé possível por no máximo alguns minutos.…”
Section: O Opo De São Paulounclassified
“…Na figura 4.7 são mostradas algumas curvas de rotação de elipse de ruído para diversas frequências de análise. Em particular,é de se notar que se torna possível girar completamente a elipse (ou seja, o coeficiente |g 1 (Ω)| 2 vai a zero para algum valor de dessintonia da cavidade) apenas para frequências de análise que satisfaçam 40) em que δωé a largura de banda da cavidade (FWHM), em total acordo com [7] (ver também figura 4.6). Isto implica que as cavidades de análise devem ter altas finesses e/ou grandes comprimentos, já que a largura de bandaé o quociente da finesse pelo intervalo espectral livre.…”
Section: Rotação Da Elipse De Ruídounclassified